Funds For Startups In Vietnam - Thy, Nguyen Thi Anh (Advances in Social Sciences Research Journal, 2019)
In the present age, startup phenomenon which is new with authors as well as investors is increasingly notable because of its nature and contribution for the nation’s economy. A lot of theoretical researches and experimental tools have been triggered to understand and foster the lives of new ventures. Among resources that startups need to survive, the important of money resource is undeniable. However, almost small businesses have a shortage of it and are difficult to reach the fulfillment of financing methods. The reasons for this are they are new and get a lot of risks which hardly meets the criterion of traditional investors. To solve the gap of fund for startups, some new financing methods are suitable and approachable, crowdfunding is one of them. This paper aims two goals, firstly, describing the increase of that new method as well as the role of it to new ventures all over the world and in Vietnam, secondly, suggesting some solution direction to improve the effectiveness of crowdfunding activities in Vietnam.